Analisis Potensi Ekowisata Dan Kesiapan Masyarakat Kecamatan Talamau Dalam Pengembangan Ekowisata - Ahmad Rasyid Ridho Agus (JURNAL DESTINASI PARIWISATA, 2022)
Ecotourism is travel to natural areas that are not disturbed and contaminated with the specifications ofobjects of education, admiration, beauty of wild plants and animals, past and present culture. Talamau Districthas a lot of tourism potential both natural tourism and cultural tourism. These natural and cultural tourismpotentials are very suitable to be developed into ecotourism which can increase the income of local people. .This study aims to determine the ecotourism potentials that exist in the Talamau District and the community'sreadiness to carry out ecotourism. This research is qualitative research with data collection techniques derivedfrom interviews, observation, and literature study. Based on the data obtained, it is known that the tourismpotential in the Talamau sub-district consists of natural and cultural potential, namely Mount Talamau, hotsprings, Sarasah waterfalls, the traditional village of Talamau village, Malopeh Kaua and Rejecting Balarituals, and the tradition of Manajalg Talu shoots. Based on the analysis conducted by researchers with theinternational ecotourism standard, it can be concluded that Talamau District is ready to develop ecotourism.Keyword: Ecotourism, Talamau, Potentials, Community Readiness